Elevated blood urea nitrogen-to-creatinine ratio predicts short-term mortality in intensive care unit patients with ischemic stroke: Evidence from a multicenter cohort - Huang Luwen; Wu Dongmei; Yu Ming; Xu Lei; Zhang Yunwei (PLoS ONE, 2025)
Background The blood urea nitrogen-to-creatinine ratio (BUCR) has emerged as a potential biomarker for predicting the prognosis of Intensive Care Unit (ICU) patients. However, its relationship with short-term mortality in patients with ischemic stroke (IS) remains controversial. This study aimed to investigate the association between BUCR and 28-day in-hospital mortality in ICU IS patients. Methods This retrospective cohort study utilized data from the eICU Collaborative Research Database (2014--2015). A total of 2,702 ICU patients with IS were included. The BUCR was calculated on the basis of initial blood urea nitrogen and serum creatinine levels obtained within the first 24 hours of ICU admission. The association between BUCR and 28-day in-hospital mortality was assessed via Cox proportional hazards regression models. Restricted cubic spline analysis was performed to evaluate potential nonlinear relationships. Sensitivity analyses—including complete-case analysis, multiple imputation, propensity score matching, and E-value estimation—were conducted to assess the robustness of the findings. Results The mean age at baseline was 68.59 years (SD: 14.29), and 313 patients (11.58%) died within 28 days of hospitalization. Compared with Q1, BUCR in Q3 was significantly associated with 28-day in-hospital mortality (HR = 1.616; 95% CI: 1.173, 2.226). After full adjustment for potential confounders, a linear relationship was observed between BUCR and mortality risk. Each unit increase in BUCR was associated with a 1.4% increase in the hazard of death (HR = 1.014; 95% CI: 1.002, 1.027; P = 0.021). Sensitivity analyses confirmed the robustness of this association. Conclusion An elevated BUCR is an independent predictor of 28-day in-hospital mortality in ICU patients with ischemic stroke. This finding provides compelling evidence to address existing inconsistencies in the field, suggesting that BUCR may serve as a simple and effective biomarker for identifying high-risk patients with severe IS.